Evolutionary conservation of Zinc-Activated Channel (ZAC) functionality in mammals: a range of mammalian ZACs assemble into cell surface-expressed functional receptors - Jensen, Anders A. (Frontiers in Molecular Biosciences, 2023)
In contrast to the other pentameric ligand-gated ion channels in the Cys-loop receptor superfamily, the ZACN gene encoding for the Zinc-Activated Channel (ZAC) is exclusively found in the mammalian genome. Human ZAC assembles into homomeric cation-selective channels gated by Zn 2+ , Cu 2+ and H + , but the function of the receptor in human physiology is presently poorly understood. In this study, the degree of evolutionary conservation of a functional ZAC in mammals was probed by investigating the abilities of a selection of ZACs from 10 other mammalian species than human to be expressed at the protein level and assemble into cell surface-expressed functional receptors in mammalian cells and in Xenopus oocytes. In an enzyme-linked immunosorbent assay, transient transfections of tsA201 cells with cDNAs of hemagglutinin(HA)-tagged versions of these 10 ZACs resulted in robust total expression and cell surface expression levels of all proteins. Moreover, injection of cRNAs for 6 of these ZACs in oocytes resulted in the formation of functional receptors in two-electrode voltage clamp recordings. The ZACs exhibited robust current amplitudes in response to Zn 2+ (10 mM) and H + (pH 4.0), and the concentration-response relationships displayed by Zn 2+ at these channels were largely comparable to that at human ZAC. In conclusion, the findings do suggest that the functionality of ZAC at the molecular level may be conserved throughout mammalian species, and that the channel thus may govern physiological functions in mammals, including humans.